Peran UNICEF Indonesia Menangani Perundungan di Sekolah Melalui Program Roots - Elsye Yubilia Keysinaya; Nuraeni (Sospol : Jurnal Sosial Politik, 2022)
This paper aims to understand the role of UNICEF Indonesia as an intergovernmental organization to solve the problem of school bullying in 2016–2020 through the Roots Program. The occurrence of school bullying in children and adolescents is an increasingly worrying phenomenon. Bullying is often being overlooked, it has a profound impact on physical and mental health, and reduces student academic performance. Addressing the problem of bullying requires efforts from various parties, including through the collaboration between the Government of Indonesia and UNICEF. This research used Ian Hurd's perspective as theoretical framework to understand the role of UNICEF Indonesia as an actor, forum, and resources through descriptive qualitative research method. Study literatures and interviews are used as data collection techniques. The results of this study found that through the Roots Program, UNICEF Indonesia tends to carry out its role as an actor.